A critical phenomenon of phase transition in hydroxyapatite investigated by thermally stimulated depolarization currents. Issue 2 (2nd November 2016) - Horiuchi, Naohiro; Iwasaki, Yuki; Nozaki, Kosuke; Nakamura, Miho; Hashimoto, Kazuaki; Nagai, Akiko; Yamashita, Kimihiro
Abstract: We observed a critical phenomenon of ferroelectric transition in hydroxyapatite (HAp) through measuring the thermally stimulated depolarization current of polycrystalline monoclinic HAp. Two peaks attributable to hydroxide (OH − ) ion dipole reorientations were observed. The one was very sharp, the other displayed a broad peak ranging from 350 to 550 K. While the broad peak can be attributed to the diffusive reorientation motions of OH − ion dipoles, the sharp peak, related to the ferroelectric phase transition, implies the presence of ferroelectricity in HAp. The sharp peak was found near 380 K, the phase‐transition temperature from the monoclinic to hexagonal is ascribed to a critical phenomenon caused by the ferroelectric behavior of OH − ion dipole reorientations.